Insect marks on bones from La Guillerma archaeological locality (Salado river depression, Buenos Aires, Argentina) - Escosteguy, Paula Daniela (2021)
The La Guillerma archaeological locality is located in the northeast sector of Buenos Aires province (Argentina). Two of its sites (LG1 and LG5), dated between ca. 1400-and 600-years BP, have a great amount of faunal remains including deer, rodents, fish and small birds that are subjected to taphonomic agents and processes (e.g., weathering, manganese, roots). Previous studies have shown osteophagic behaviour in different insects (e.g., Coleoptera, Blattodea). In this paper, we evaluate their incidence on La Guillerma faunal assemblage. We performed an analysis on marks that were identified in bone remains of various taxa and applied the criteria for identifying bone alteration by insects (i.e., by measuring each trace and comparing them with the types of insect marks described in the literature). Fifteen specimens (LG1 = 6 and LG5 = 9) exhibited different types of modifications (e.g., pits with striae in base, pits with emanating striae, striations) that are related to the action of insects. Although the proportion of affected bones is low in relation to the total sample, we highlight our study as the first detailed analysis of insect marks on archaeological bones from Argentina. We also emphasize the significance of addressing insect-produced modifications on Argentinean archaeological sites.